Hepatitis C in HIV-1 virus users using drugs in Piauí, Brazil (Research, Society and Development, 2021)
This scientific research aimed to assess and identify important epidemiological aspects of HCV and HIV infections in HIV-AIDS patients using illicit drugs in the state of Piauí, as well as to identify risk factors for co-infection. The research was developed in two stages: (1) Formation of a database from secondary data and (2) Analysis / Disclosure. The first stage of the study consisted of the formation of a database based on epidemiological information and diagnosis of the population of patients infected with the HIV virus using drugs in the state of Piauí. The 2nd stage of the study, on the other hand, consisted of analyzing the data collected in the 1st stage and beginning to disclose the results of the study. The socio-demographic variables of individuals with HIV / HCV in Piauí were higher in males, aged over 40 years, black/brown. As for the significant association regarding exposure to HIV infection in Piauí, there is a greater relevance for sexual relationships with users of illicit drugs, surgery, sexual preference and STDs. Both of which contribute to the evolution of the epidemic, mainly because it is related to risky sexual behavior. It is not possible to identify a single factor responsible for co-infection. In short, this proposal contributed with relevant epidemiological information on the population of HIV-AIDS patients using illicit drugs and infections caused by the HIV / HCV viruses.